Weighted corporate social responsibility index for measuring Islamic banking's social performance: how to develop it? - Shahabuddin, Abu Saim Mohammad; Alamer, Abdullah Rajeh Ali; Abd Sukor, Mohd Edil; Niaz Ahmad, Mohd Naseem (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
It is posited that Islamic Banking is meant to be socially responsible. Relating to this social responsibility, this paper undertakes two objectives. One is to develop an illustration of a corporate social responsibility (CSR) measurement index by allocating differential weights to process-based and outcome-oriented CSR measures. The illustrative index contains nine (9) process-based measurement items, which fall under three (3) dimensions: investment, research and development, and human resources. Outcome-oriented measurement items are eight (8), which represent three (3) dimensions: Shariah Supervisory Board (SSB), social activities and sharing, and environment. The way of deciding different weights for these two categories of measures is explained, and a possible method for validation of assigned weights is proposed. Another objective is to explain why CSR measures relating to core business processes should be given more weight than outcome-oriented CSR measures for Islamic banks. In order to develop this explanation, the paper draws upon Quranic and Hadith texts, maqasid literature and published works on CSR of Islamic banks. The basic argument underlying this explanation is that purity of the process of earning is a precondition for the earning-based beneficial acts to be acceptable as good deeds.